Malcolm Darling and Developmentalism in Colonial Punjab*. (12th January 2018) - SULTAN, ATIYAB
Abstract: This article studies the career and writings of Sir Malcolm Darling to make three main claims. First, an intellectual genealogy of development studies is presented through the examination of close parallels between colonial efforts at rural welfare and post-colonial prescriptions for the same. Darling was central in the British efforts in Punjab to formulate ideas of reform from below or thrift among the peasantry, both of which remain popular in contemporary theories of community development and microfinance respectively. The similarities between colonial and post-colonial reforms are striking because the colonial experience remains largely forgotten. This intellectual amnesia serves a political end by blaming the peasant for his poverty and redemption from the same. Simultaneously, any structural or revolutionary social change is avoided. Secondly, the article probes the exaggerated focus on indebtedness and the political interests this served. Indebtedness gave the Unionists in Punjab political legitimacy, and the colonial state formulated solutions for the problem that did not tax its resources, for example the cooperative movement was designed to be self-financing. Finally, the article speaks to the themes of this issue by challenging the assumption that 'institutions' alone are a legacy of colonial rule and developmentalist reform is a post-colonial preoccupation of independent states. By presenting a case study of attempted economic and institutional reform during colonial rule, it allows one to appreciate the close, contemporaneous connections between colonial modes of governance and current modes of development.